Penyuluhan Stunting di Kelurahan Padang Matinggi Kecamatan Rantau Utara - Rani Darma Sakti Tanjung; Halimah Tusyadiah Harahap; Rika Handayani; Junaidi Junaidi (STIKES Columbia Asia Medan, 2025)
Counseling is an effective method to increase public knowledge about stunting prevention. This study aims to enhance the understanding of the community, especially pregnant women and health cadres, in Kelurahan Padang Matinggi, Kecamatan Rantau Utara, regarding the importance of stunting prevention. The method used in this activity is interactive counseling, which includes lectures, educational videos, educational games, and role play. A pre-test was conducted before the counseling to measure participants' initial knowledge, and a post-test was administered after the counseling to assess the increase in participants' knowledge. The results showed a significant improvement in participants' knowledge, with the average score increasing from 81.1 in the pre-test to 96.6 in the post-test (p=0.002). This counseling successfully raised community awareness about the importance of balanced nutrition and stunting prevention, as well as encouraged health cadres to be more active in spreading this information within the community. The success of this activity demonstrates that a community-based and participatory approach can be an effective strategy in preventing stunting.